lncRNA Helf promotes hepatic inflammation and fibrosis by interacting with PTBP1 to facilitate PIK3R5 mRNA stabilization - Xiaohui Han; Beichen Guo; Sicong Zhao; Yehua Li; Jing Zhu; Yifan He; Jiajun Wang; Qingbin Yao; Shuai Shao; Lina Zheng; Zhemin Shi; Tao Han; et al. (Cellular & Molecular Biology Letters, 2023)
Abstract Background Hepatic fibrosis is a common consequence of chronic liver diseases without approved antifibrotic therapies. Long noncoding RNAs (lncRNAs) play an important role in various pathophysiological processes. However, the functions of certain lncRNAs involved in mediating the antifibrotic role remain largely unclear. Methods The RNA level of lnc-High Expressed in Liver Fibrosis (Helf) was detected in both mouse and human fibrotic livers. Furthermore, lnc-Helf-silenced mice were treated with carbon tetrachloride (CCl4) or bile duct ligation (BDL) to investigate the function of lnc-Helf in liver fibrosis. Results We found that lnc-Helf has significantly higher expression in human and mouse fibrotic livers as well as M1 polarized hepatic macrophages (HMs) and activated hepatic stellate cells (HSCs). In vivo studies showed that silencing lnc-Helf by AAV8 vector alleviates CCl4- and BDL-induced hepatic inflammation and fibrosis. Furthermore, in vitro experiments revealed that lnc-Helf promotes HSCs activation and proliferation, as well as HMs M1 polarization and proliferation in the absence or presence of cytokine stimulation. Mechanistically, our data illustrated that lnc-Helf interacts with RNA binding protein PTBP1 to promote its interaction with PIK3R5 mRNA, resulting in increased stability and activating the AKT pathway, thus promoting HSCs and HMs activation and proliferation, which augments hepatic inflammation and fibrosis. Conclusion Our results unveil a lnc-Helf/PTBP1/PIK3R5/AKT feedforward, amplifying signaling that exacerbates the process of hepatic inflammation and fibrosis, thus providing a possible therapeutic strategy for hepatic fibrosis.